Governança corporativa em empresas brasileiras como determinante da evidenciação de benefícios a empregados - Acimelly Raíza de Araújo Carneiro; Patrícia Vasconcelos Rocha Mapurunga; Vera Maria Rodrigues Ponte; Cinthya Rachel Firmino de Morais (Revista Contemporânea de Contabilidade, 2013)
The research aimed to raise the degree of compliance with the disclosure guidelines defined in the CPC 33 companies listed on the BM & FBovespa, and investigate whether there was greater compliance with these guidelines by companies participating in the Differentiated Levels of Corporate Governance. Methodologically, were used bibliographic and documentary procedures and nonparametric hypothesis tests and correspondence analysis, gathering a sample of 366 companies. There was low compliance with the disclosure requirements. Furthermore, there was greater compliance with the requirements for companies of different levels, and an association between firms with greater adherence to CPC 33 and those of the New Market.